A Graphical Diagnostic Test for Two-Way Contingency Tables (2016)
We propose and illustrate a new graphical method to perform diagnostic analyses in two-way contingency tables. In this method, one observation is added or removed from each cell at a time, whilst the other cells are held constant, and the change in a test statistic of interest is graphically represented. The method provides a very simple way of determining how robust our model is (and hence our conclusions) to small changes introduced to the data. We illustrate via four examples, three of them from real-world applications, how this method works